Use of chestnut propolis extract produced by maseration, reflux and ultrasound-assisted extraction methods in different food models: Effect on physicochemıcal, sensory and bioactive properties - Şenol Yazkan, Sevde Nur; Hendek ertop, Müge (Scientific Web Journals (SWJ), 2024)
This study obtained ethanol-extracted propolis by applying maceration, reflux, and ultrasound-assisted extraction methods to propolis obtained from chestnut honey hives. Chestnut propolis extracts prepared by the methods were added to flower and chestnut honey at four different rates (0, 1, 2 and 4%) as a food model without heat treatment, and antioxidant activity, total phenolic content, colour, and sensory analysis of honey mixtures were made. Although the antioxidant activity (AO) (82.96%) and total phenolic content (TPC) (412.50 µg GAE /g) of chestnut honey were higher than that of flower honey (AO: 49.69%, TPC: 127.50 µg GAE/g), it was determined that the bioactive properties of flower honey (AO: 90.00%, TPC:713.60 µg GAE/g) rose close level to that of chestnut honey (AO:89.08%, TPC: 849.17 µg GAE/g) thanks to the addition of 4% propolis extract. Because the colour of chestnut honey with high colour intensity (1803.5 mAU) is significantly darker than flower honey (378.5 mAU), the different addition rates and extraction method of propolis did not significantly affect the final product colour intensity of chestnut honey (p>0.05), the addition of propolis in flower honey increased the colour intensity significantly (p<0.05). When propolis extracts prepared with three extraction methods are added to the basic cake formulation as a heat-treated food model in 4 different ratios (0, 1, 2 and 4%), the bioactive properties of the products (AO: 11.97%, TFM: 285.0 µg GAE/g) were determined to increase depending on the increasing propolis addition rate. Although propolis increases the antioxidant activity and phenolic substance content of the food models to which it is added due to its rich bioactive content, sensory properties of the food models were analysed due to propolis extracts' unique, intense taste, colour and flavor, and the results were evaluated with Principal Component Analysis. In terms of both food models, the products with propolis produced by maceration extraction had higher sensory evaluation scores. In contrast, the control samples without propolis were found to be similar to the products with 1% and 2% propolis added, respectively. The products with 4% propolis added showed separate clustering with low evaluation scores.
Keywords: Gıda Teknolojileri; Food Technology; Kestane propolis; Arı ürünleri; Bal; Fırıncılık ürünleri; Chestnut propolis; Bee products; Honey; Bakery products; 2. Zero hunger